NIHAO XV: the environmental impact of the host galaxy on galactic satellite and field dwarf galaxies - Buck, Tobias; Frings, Jonas (Monthly notices of the Royal Astronomical Society, 2019)
Abstract. We study the impact of the host on dwarf galaxy properties using four new Milky Way (MW)-like, ultra-high-resolution simulations (Npart > 107) fro